Ectopic ossification presenting as osteoid metaplasia in a salivary mucocele in a Shih Tzu dog - Fernandes, Thais R. [UNESP]; Grandi, Fabrizio [UNESP]; Monteiro, Lidianne N. [UNESP]; Salgado, Breno S. [UNESP]; Rocha, Rafael M.; Rocha, Noeme Sousa [UNESP] (Biomed Central Ltd., 2012)
Background: Salivary mucocele is an accumulation of saliva in a single or multiloculated cavity lined by connective tissue that is contiguous to a salivary gland-duct complex and is the most common condition affecting the salivary glands in dogs. Occasionally, different types of metaplastic lesions, such as squamous and osseous metaplasia - which are rare lesions in animals - can be observed in association with salivary mucocele.Case presentation: A right facial enlargement was suddenly observed in a 4-year-old non-spayed female Shih-Tzu dog. The lesion presented itself as a soft and fluctuant mass located in the right side of the face near to the neck. Histologically, the mass consisted of a cavitary formation without an epithelial lining. Additionally, microscopic examination revealed the presence of osteoid-producing cells which gave rise to areas of bone formation, probably induced by irritation due to the presence sialoliths. Such cells and bone formations were also present in the cavity wall, consequently leading us to classify the condition as a salivary mucocele with osseous metaplasia.Conclusions: In the present case, the pathogenesis was probably associated with the presence of sialoliths, which can behave as etiological agents for the metaplastic lesion. The occurrence of osteoid metaplasia is a rare peculiar condition in the canine salivar y gland, and due to the rarity and lack of information about this specific disease, no clinical data can yet be associated with the development of salivary mucocele with osseous metaplasia in dogs.